Analisis Campuran Tanah Liat dan Batu Kapur Bukit Pecatu Sebagai Instrumen Pemanen dan Penampung Air Hujan - Wijayanti, Ni Wayan Eka; Eka Suryana, I Gede Putu (International Journal of Natural Science and Engineering, 2020)
This research originated from the large number of limestone mining in the Pecatu Hill area and it caused deep niches. On the other hand, the problem of water scarcity is the main thing, because the characteristics of karst rocks can escape, dissolve and absorb water. The condition of the ex-niche mining and water shortages are two different problems. But in this study, trying to combine these problems into a solution with the aim of making experiments that can make limestone from Pecatu Hill have the potential to hold water for a long time in the form of a miniature reservoir model. This miniature reservoir model is made with a mixture of clay suspensions of various concentrations (0%, 5%, 10% and 15%). This miniature reservoir model is tested for discharge and absorption of water which is assumed to be rainwater puddle to determine the ability to absorb rainwater. The result of this test is that the miniature reservoir with a mixture of 15% clay suspension has the ability to withstand a decrease in rainwater shrinkage of 0.04L / minute and has a small water absorption capacity of 10.91% compared to other concentrations. This shows that the miniature limestone reservoir of Pecatu Hill with a mixture of 15% clay suspension has potential as an instrument for harvesting and collecting rainwater. So this is expected to be utilized by the villagers of Pecatu Hill as an instrument for harvesting and collecting rainwater.